6 февраля, 18:38

Упростите выражения: 0,2-2t+1/5t - 3 (m+4) + 2m

+2
Ответы (1)
  1. 6 февраля, 20:05
    0
    Упростим выражения:

    1) 0,2 - 2 * t + 1/5 * t = 0.2 - 2 * t + 0.2 * t = 0.2 + (-2 * t + 0.2 * t) = 0.2 + t * (-2 + 0.2) = 0.2 + t * (-1.8) = 0.2 - 1.8 * t;

    2) Раскроем скобки в выражении - 3 * (m + 4) + 2 * m.

    -3 * (m + 4) + 2 * m = - 3 * m - 3 * 4 + 2 * m = - 3 * m - 12 + 2 * m;

    Приведем подобные значения.

    (-3 * m + 2 * m) - 12 = m * (-3 + 2) - 12 = m * (-1) - 12 = - m - 12.
Знаешь ответ на этот вопрос?